Legal Relations Between Drivers and Online-Based Transportation Companies - Mukhammad Amri; Sri Anggraini Kusuma Dewi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
The purpose of this research is to find a form of legal protection for online motorcycle taxi drivers called partnerships. This research method combines normative juridical research methods. What is meant by normative juridical research is research based on document study studies that collect literature study materials related to the discussion and processing of the journal material by using the descriptive method by looking at problems that occur in the midst of people's lives, the focus of the study stems from regulatory provisions applicable laws and regulations, accompanied by theories and legal principles related to the problem under study. The results of the electronic agreement (e-contract) between PT. GOJEK, AKAB, and GOJEK's prospective partners have clauses that can be categorized as standard clauses which in fact are prohibited in Law Number 8 of 1999 concerning Consumer Protection and contain the principle of mutualism in which the agreement is mutually beneficial between the two parties. So in the agreement it can be said that PT. GOJEK Indonesia is not fully responsible when GOJEK partners experience fictitious orders because the agreement contains the principle of mutualism and is prohibited by Law Number 8 of 1999 concerning Consumer Protection.